B. Delbrück’s Gesetz der Occasionellen Wortstellung (Atti del Sodalizio Glottologico Milanese, 2017)
Delbrück’s work about Indo-European syntax, especially his contribution to the analysis of Vedic syntax, is still a useful tool for those who want to deal with the study of ancient Indian syntax, with particular reference to methodological analysis of constituent order. In fact, the notions of basic and marked word order of sentences are already present in Delbrück’s perspective, along with the idea of constituent movements motivated, albeit through mechanisms of prosodic order, by the interface between syntax and information structure of the sentence. His most general law of Occasionelle Wortstellung should probably be differentiated into a set of movements of constituents, which can correspond to sentence orders functionally differentiated. However, the idea of reducing the apparent constituents order freedom of Vedic sentence to the interaction between a general basic word order and a general principle of movement determined by sentence information structure, makes Delbrück a true founder of the modern studies about sentence syntax. KEYWORDS: Berthold Delbrück, Vedic syntax, Śatapathabrāhmaṇa, syntactic movement, Neogrammarian linguistics